An action research and scaffolding based approach for maritime design education: a contribution towards shaping ships for people. Issue 3 (2nd July 2020) - Abeysiriwardhane, Apsara; Lützhöft, Margareta; Ghosh, Samrat
ABSTRACT: This paper presents the results of a research study conducted aiming to educate maritime design students with maritime Human Factors (HF) and Human-Centred Design (HCD) theoretical concepts and to motivate them to utilise that knowledge in the design process. The final year maritime design students at the Australian Maritime College were facilitated throughout a year of a planned HCD scaffolding program based on a pedagogical framework. Action Research was used as the methodological framework, which is considered appropriate for studying the effectiveness of a teaching intervention. The overall effect of the program was determined through records maintained in the researcher's journal, response from a questionnaire, an interview, and from the results of a design project report review. The findings demonstrated that the contribution of such a program raised awareness and understanding of HCD and maritime HF among the students. Also, the findings of this paper highlighted the fact that the fresh mind of a maritime design undergraduate is the best state to integrate HF and HCD knowledge which provides enduring benefits for the industry and for shaping ships for people. Besides, possible improvements for future delivery of this program were also identified.